A MACRO-COMPARATIVE ASSESSMENT OF WELFARE STATE CONVERGENCE IN THE EUROPEAN UNION - OROSZ Ágnes; SZIJÁRTÓ Norbert (Management of Sustainable Development, 2021)
In this paper, we provide a macro-comparative assessment of welfare state convergence. Using the welfare state regime approach, the paper analyses the development of main welfare state indicators within in the enlarged European Union. In this study we capitalize on descriptive statistics and a single convergence analysis based on standard deviation in order to capture alterations in national welfare models of 26 European countries and among acknowledged welfare regimes. Our fundamental aim is to seize on long-term processes (convergence, divergence, or persistence), so we cover almost a two-decade period starting at 2000. Our results, in general, suggest that convergence among welfare states (different indicator of social spending) of European countries is particularly weak, however convergence inside welfare regimes is significantly stronger apart from the Anglo-Saxon group. The pre-crisis period was characterized by a stronger convergence among European countries as a consequence of economic prosperity and intense EU intervention.